LEADME : an educational software for composite laminate analysis and design - Mohamed Ali, Jaafar Syed; Abeid Abeid , Rubeya (Trans Tech Publications, Switzerland, 2015)

(untitled)
LEADME (Laminate Analysis and Design Made Easy), an educational software useful for the analysis and design of laminated composite structure has been developed. The software encompasses both the micro and macro mechanics analysis of lamina and laminate. The highlight of this software is that, apart from usual laminate analysis, the software is capable to solve practical laminate applications such as analysis of beams and also a design module is included. The software has been developed using MATLAB-Graphical User Interface (GUI) which makes it very user friendly. The results obtained from this software have been validated. It is expected that this software will serve as an educational tool complementing textbooks for students to gain better understanding of composite structural analysis.